MARKET RISK ESTIMATION IN (T+)-TRANSACTIONS - Radik B. Begov; Michael N. Prokofyev; Alexander S. Trusov (Модернизация, инновация, развитие, 2016)
Market risk analysis and estimation are presentedin T+ transactionsas they are used within the Moscow Exchange. There is a need to do so as a result of the cut-off of a new REPO product with Central Counterpartner (CCP). Here repurchase agreement goes through the National Clearing Center (NCC), the last being a bank and a clearing structure within the Moscow Exchange group.NCC actsas an intermediary (so called “Central Counterpartner”) between trading participants.REPOs with CCP raisecontractor claims and commitments to the CCP which takes the risk of default on commitments from unfair contract side. The REPO with CCP cut-off made ready a technological platform to implement T+2 trades at the Moscow Exchange. As a result of it there appeared the possibility to enter security purchase/sell contracts partially collateralized. All these transactions (the REPO with CCP, T+) made it a must determining security market risks. The paper is aimed at presenting VaR-like risk estimates. The methods used are from the computer fi nance. Unusual TS rate of return indicator is proposed and applied to find optimal portfolios under the Markowitz approach and their VaRs (losses) forecasts given the real “big” share price data and various horizons. Portfolio extreme rate and loss forecasting is our goal. To this end the forecasts are computed for three horizons (2, 5 and 10 days) and for three significance levels.There were developed R-, Excel- and Bloomberg-basedsoftware tools as needed. The whole range of proposed computing steps and the tables with charts may be considered as candidates to be included in the future market risk standards.Paper results permit capital market participants to choose the correct (as to the required risk level) common stocks.